EFEKTIVITAS DAKWAH BAGI REMAJA - Asmaya, Enung (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2013)
Bad behavior is basically a result of personal interaction with physical environment,that is one’s perception to the object. The trasitional age of adolescence and the environementfactor may support vandalism or juvenile deliquency. The changes of feeling and thinkingoften make adolescence feel shocked, worried, and scared in a certain time, but they can alsobe very brave and patriotic.In the society, bad and good behavior (munkar and ma’ruf) are performed by all agelevels of society, from shildhood to adult. However, adolescence tend to be very unstable todo some bad behavior such as pacaran (dating), fighting, free sex, using drugs, rape, tellinglies, not keeping promise, not discipline, lazy to perform religious rules, and vandalism.